Determination of trace aflatoxin levels in agricultural products and foodstuffs using ELISA system after immunoaffinity clean-up procedure - Bakirdere, S.; Yaroglu, T.; Tirik, N.; Demiroz, M.; Karaca, A. (Edizioni Minerva Medica, 2014)
Total aflatoxin level as naturally occurring mycotoxin were determined in different foodstuffs such as apricot, figs, raisins, peanut butter, bread, tahin-pekmez (sesame oil-molasses) and red paprika commonly consumed in Turkey. Immunoaffinity column was used to eliminate or minimize the interferences coming from the matrix by cleaning-up the samples prior to measurement step. Recovery experiments were performed to check the reliability of the column clean-up procedure. Accuracy of the method was also checked by using rice as test material (T04151) and the results found were in good agreement with the certified value. Concentration of aflatoxins was found to be higher than quantitation limit in most of the bread samples. The highest concentration of aflatoxin was found in raisin as 3.90 mu g kg(-1) while aflatoxin level ranged between 0.72-2.30 mu g kg(-1) in red paprika.
Keywords: Aflatoxins; Food; Aflatoxins